VD_FINDINFO Arrêt / 2010 / 710 vom 25. März 2010 - VD Tribunal cantonal (2010)
AA, TRAITEMENT DES SUITES D'UN ACCIDENT, CARACTÈRE SCIENTIFIQUEMENT RECONNU | 10 al. 1 let. a LAA, 32 al. 1 LAMal, 33 LAMal, 56 al. 1 LPGA, 33 let. a OAMal, 33 let. c OAMal, 1 OPAS, 117 al. 1 LPA-VD, 93 al. 1 let. a LPA-VD